Językowo-kulturowy obraz wdowieństwa w polszczyźnie ogólnej - Skorupska-Raczyńska, Elżbieta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The stereotype of widowhood was shaped centuries ago, initially and primarily concerning widows, with widowers being included much later. Its reflection can be found in lexicon, phraseology and paremiography. It has been popularized in literature and artistically reproduced: the widow is generally discredited, while the widower is often valorized, regardless of his financial status, age or family relationships. Despite civilizational progress and the widely-promoted equality ideologies, we would not, in the first instance, entrust our financial assets to them (widows and widowers); they remain somewhat reserved. Widows are often seen taking care of the home and children. Both widows and widowers are deemed suitable for undertaking the demanding and difficult care for the chronically ill. In the functioning phraseology and proverbs related to widowhood, we find one unequivocally positive expression, wdowi grosz (“widow’s mite”), of biblical origin. The analysis of the linguistic image of widowhood found in proverbs, idioms and phrases was conducted primarily using material from the four-volume Nowa księga przysłów i wyrażeń przysłowiowych polskich (New book of Polish proverbs and proverbial expressions), published between 1969 and 1978, edited by Julian Krzyżanowski, and from the two-volume Słownik frazeologiczny języka polskiego (Phraseological dictionary of the Polish language) by Stanisław Skorupka from 1974. Additional studies and Polish language dictionaries were also used as supplementary sources. Both the portrayal of widowhood in classic literature and the results of a survey confirmed the persistence of its stereotype.